This preview shows pages 1–3. Sign up to view the full content.
This preview has intentionally blurred sections. Sign up to view the full version.
View Full Document
Unformatted text preview: CMPS 101 Midterm 1 Review Solutions to selected problems Problem 2 State whether the following assertions are true or false. If any statements are false, give a related statement which is true. a. )) ( ( ) ( n g O n f = implies )) ( ( ) ( n g o n f = . False )) ( ( ) ( n g o n f = implies )) ( ( ) ( n g O n f = b. )) ( ( ) ( n g O n f = if and only if )) ( ( ) ( n f n g Ω = . True c. )) ( ( ) ( n g n f Θ = if and only if L n g n f n = ∞ → )) ( / ) ( ( lim , where ∞ < < L . False ∞ < < L and L n g n f n = ∞ → )) ( / ) ( ( lim implies )) ( ( ) ( n g n f Θ = Problem 3 Prove that )) ( ) ( ( )) ( ( )) ( ( n g n f n g n f ⋅ Θ = Θ ⋅ Θ . In other words, if )) ( ( ) ( 1 n f n h Θ = and )) ( ( ) ( 2 n g n h Θ = , then )) ( ) ( ( ) ( ) ( 2 1 n g n f n h n h ⋅ Θ = ⋅ . Proof: By hypothesis there exist positive constants 1 n , 2 n , 1 a , 1 b , 2 a , and 2 b such that ) ( ) ( ) ( : 1 1 1 1 n f b n h n f a n n ≤ ≤ ≤ ≥ ∀ and ) ( ) ( ) ( : 2 2 2 2 n g b n h n g a n n ≤ ≤ ≤ ≥ ∀ If ) , max( 2 1 n n n n = ≥ , then both inequalities hold. Let 2 1 a a c = , and 2 1 b b d = . Since everything in sight is nonnegative, we can multiply these two inequalities to get ) ( ) ( ) ( ) ( ) ( ) ( : 2 1 n g n f d n h n h n g n f c n n ≤ ≤ ≤ ≥ ∀ , and hence )) ( ) ( ( ) ( ) ( 2 1 n g n f n h n h ⋅ Θ = ⋅ as required. /// Problem 4 Let ) ( n f and ) ( n g be asymptotically positive functions (i.e. ) ( > n f and ) ( > n g for all sufficiently large n ), and suppose that )) ( ( ) ( n g n f Θ = . Does it necessarily follow that Θ = ) ( 1 ) ( 1 n g n f ? Either prove this statement, or give a counterexample. Solution: The statement is true , as we now prove. By hypothesis there exist positive numbers 1 c , 2 c , and n such that for all n n ≥ : ) ( ) ( ) ( 2 1 n g c n f n g c ≤ ≤ < . (Note: the strict inequality < on the left follows from the fact that ) ( n f and ) ( n g are asymptotically positive.) Taking the reciprocals of all the positive terms in this inequality gives: ) ( 1 1 ) ( 1 ) ( 1 1 1 2 n g c n f n g c ⋅ ≤ ≤ ⋅ < for all n n ≥ . Observe that both 1 2 > c and 1 1 > c , whence Θ = ) ( 1 ) ( 1 n g n f . /// Problem 5 Let ) ( n g be an asymptotically nonnegative function. Prove that...
View
Full
Document
This note was uploaded on 11/16/2009 for the course CMPS 101 taught by Professor Tantalo,p during the Fall '08 term at University of California, Santa Cruz.
 Fall '08
 Tantalo,P

Click to edit the document details